2017
DOI: 10.21608/ejrs.2017.46587
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF GARLIC (Allium sativum) TREATMENT ON HEMATOLOGICAL, BIOCHEMICAL, HORMONAL AND FERTILITY PARAMETERS OF MALE BOUSCAT RABBITS

Abstract: The present study was carried out on a flock of Bouscat rabbits belongs to El

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The present study findings tie with prior research on the antioxidant properties of herbal plants extract, which were also well demonstrated in this study. Allicin, alliin, allyl disulfide, and allyl cysteine are antioxidant chemicals found in garlic (Elkelawy et al, 2017). Benzie and Wachtel-Galor (2011) reported that turmeric extracts can scavenge free radicals, increase antioxidant enzymes, and inhibit lipid peroxidation, whereas turmeric extract (1.66 mg/kg of body weight) in rabbits high-fat diet, oxidation of erythrocyte membranes was found to be significantly lower than that in membranes of control animals.…”
Section: Advances In Animal Andmentioning
confidence: 99%
“…The present study findings tie with prior research on the antioxidant properties of herbal plants extract, which were also well demonstrated in this study. Allicin, alliin, allyl disulfide, and allyl cysteine are antioxidant chemicals found in garlic (Elkelawy et al, 2017). Benzie and Wachtel-Galor (2011) reported that turmeric extracts can scavenge free radicals, increase antioxidant enzymes, and inhibit lipid peroxidation, whereas turmeric extract (1.66 mg/kg of body weight) in rabbits high-fat diet, oxidation of erythrocyte membranes was found to be significantly lower than that in membranes of control animals.…”
Section: Advances In Animal Andmentioning
confidence: 99%
“…Garlic contains antioxidant compounds, including allicin, alliin, allyl disulfide and allyl cysteine (Elkelawy et al, 2017). The chemical reaction between nitrate and food amines that occurs in the stomach yields free radicals and nitrosamines, which induce the lipid peroxidation of multiple organs, particularly the liver and kidneys (Choi et al, 2002).…”
Section: Figure 2amentioning
confidence: 99%
“…(2018). In this concern, there is confliction in the results obtained on the effect of different doses of garlic or turmeric on performance of rabbit bucks (El‐Kelawy et al., 2017; Ogbuewu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The positive impacts of phytogenic extracts on semen quality of rabbits were reported by Mohammed et al (2018). In this concern, there is confliction in the results obtained on the effect of different doses of garlic or turmeric on performance of rabbit bucks (El-Kelawy et al, 2017;Ogbuewu et al, 2017).…”
mentioning
confidence: 99%